Analysis of volume‐to‐surface ratio effects on methane oxidative coupling using microkinetic modeling. Issue 7 (25th March 2018) - Alexiadis, V. I.; Serres, T.; Marin, G. B.; Mirodatos, C.; Thybaut, J. W.; Schuurman, Y.
Abstract : The effect of the volume‐to‐surface (V/S) ratio on the catalytic performance of a La–Sr/CaO catalyst in a fixed bed reactor under oxidative coupling of methane (OCM) conditions is investigated by adjusting the amount of diluent in the catalyst bed. It was observed experimentally that the catalyst activity, C2 selectivity, and C2 H4 /C2 H6 ratio are all favored at high V/S ratios. The total void volume, available in the intraparticle and the interstitial phase, was considered. A comprehensive OCM microkinetic model, explicitly distinguishing between these two phases, allowed accounting for the observed dependence of catalytic performance on V/S ratio. The major experimentally implemented variation in interstitial volume available for reaction, provoked also changes in radical concentration profiles in intraparticle phase. Given the high reaction rates occurring at this location, the experimentally observed effects with varying the V/S ratio, are attributed to concentration and, hence, reaction rate changes occurring mainly in the intraparticle phase. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2603–2611, 2018